1994
DOI: 10.1093/nar/22.9.1670
|View full text |Cite
|
Sign up to set email alerts
|

Increased removal of 3-alkyladenine reduces the frequencies ofhprtmutations induced by methyl- and ethylmethanesulfonate in Chinese hamster fibroblast cells

Abstract: (EMS), N-nitroso-N-methylurea (NMU) and N-nitroso-N-ethylurea (NEU) exposure. Tag expression reduced the frequency of MMS and EMS induced mutations to about half the normal rate, whereas the mutation frequency in cells exposed to NMU or NEU is not affected by the tag+ gene expression. These results indicate that after exposure to compounds which produce predominantly Nalkylations in DNA, a substantial proportion of the mutations induced is formed at 3-alkyladenine residues in DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This implies that the highly mutagenic lesion O 6 -meG, which gives rise to GC3AT transitions (45), is not repaired and therefore dominated the induction of mutations. Furthermore, expression of the tag gene in these cells did reduce the mutagenicity of MMS by a factor of 2, implicating 3-meA as the likely mutagenic lesion (28). Furthermore, a role for 3-ethyladenine in the induction of mutations by ethylating agents has also been proposed by Op het Veld et al (40).…”
Section: Vol 18 1998 Mutation Induction In Apng Knockout Mice By MMmentioning
confidence: 80%
See 1 more Smart Citation
“…This implies that the highly mutagenic lesion O 6 -meG, which gives rise to GC3AT transitions (45), is not repaired and therefore dominated the induction of mutations. Furthermore, expression of the tag gene in these cells did reduce the mutagenicity of MMS by a factor of 2, implicating 3-meA as the likely mutagenic lesion (28). Furthermore, a role for 3-ethyladenine in the induction of mutations by ethylating agents has also been proposed by Op het Veld et al (40).…”
Section: Vol 18 1998 Mutation Induction In Apng Knockout Mice By MMmentioning
confidence: 80%
“…Although increased levels of DNA repair activities, including APNG, were observed in nitrogen mustard-resistant B lymphocytes (20) and N- (2-chloroethyl)-Nnitrosourea (CNU)-resistant gliomas (34), overexpression of human APNG in Chinese hamster ovary cells afforded no protection against the cytotoxic effects of CNU or nitrogen mustards (5). Similarly, while the overexpression of the Escherichia coli tag gene, which codes for a 3-meA-DNA glycosylase with a narrow substrate specificity (1), reduced the toxic and mutagenic effects of methylating agents in Chinese hamster V79 cells (27,28), no difference in the cytotoxicities of these or other alkylating agents was found in tag-transfected NIH 3T3 murine fibroblasts (23). Furthermore, while the expression of the Saccharomyces cerevisiae MAG gene in glycosylase-deficient S. cerevisiae cells or E. coli cells protected against methylating-agent and CNU cytotoxicity (9,35), overexpression of human APNG in Chinese hamster ovary cells resulted in greater sensitivity to cell killing by methyl methanesulfonate (MMS) and an increased frequency of chromosomal aberrations (13).…”
mentioning
confidence: 99%
“…The substrate specificities of these enzymes are, however, usually much wider (Figure 2). 3-MeA has been demonstrated to be a major cytotoxic and mutagenic DNA lesion [107,108], although it is estimated to be some 40-fold less mutagenic than O'-methylguanine (O'-meG) [108], which is directly dealkylated by an alkyltransferase.…”
Section: Dna Glycosylases For Alkylated Basesmentioning
confidence: 99%
“…[149] have reported that overexpression of the TAG gene in mammalian cells may in fact increase resistance to the genotoxic effects of methylating agents such as MMS. TAG expression reduced the frequency of MMS‐ and EMS‐induced mutations at the HPRT locus to about half the normal rate [150]. Another group was, however, unable to obtain the same results with 3T3NIH murine fibroblasts [151].…”
Section: Overexpression Of Enzymes Involved In Repair Of Endogenous Dmentioning
confidence: 99%